Evaluation of bacterial transmission to the paranasal sinuses through sinus irrigation. Issue 8 (17th March 2016) - Hauser, Leah J.; Ir, Diana; Kingdom, Todd T.; Robertson, Charles E.; Frank, Daniel N.; Ramakrishnan, Vijay R.
Abstract : Background: Saline nasal irrigation is effective in the treatment of sinonasal disorders, including chronic rhinosinusitis (CRS). Despite bacterial contamination in rinse bottles and reports of infections from contaminated irrigation water, tap water is still used by ∼50% of irrigation users, raising a potential public health concern. This study aimed to determine whether bacteria from the water supply used in sinus irrigations colonizes the paranasal sinuses. Methods: Samples were taken from the: (1) water used for irrigation, (2) faucet or container the water originated from, (3) rinse bottle, and (4) postoperative ethmoid cavity from 13 subjects with CRS. Microbiota were characterized using quantitative polymerase chain reaction (qPCR) and 16S ribosomal RNA (rRNA) gene sequencing. The Morisita‐Horn beta‐diversity index (M‐H) was used to assess similarity in microbiota between samples, and genomic analysis was performed to assess clonality of cultured bacteria. Results: Of 13 subjects, 6 used distilled water, 6 used tap water, and 1 used well water in this institutional review board (IRB)‐approved observational study. Well‐water had markedly more bacteria than tap or distilled water. There was a trend toward tap having more bacteria than distilled water. The sinus samples were notably dissimilar to the bottle, faucet, and irrigant (M‐H 0.15, 0.09, and 0.18, respectively). There was no difference in postoperative microbiotas between distilled and tap water users. Conclusion: The current study suggests that irrigation plays little role in establishing the sinus microbiome. Although rinsing with tap water may never be formally recommended, these data are useful to counsel patients who prefer to do so in non‐endemic areas if the municipal water supply is appropriately treated.